2015 IEEE Global Communications Conference (GLOBECOM) 2014
DOI: 10.1109/glocom.2014.7417026
|View full text |Cite
|
Sign up to set email alerts
|

PGuide: An Efficient and Privacy-Preserving Smartphone-Based Pre-Clinical Guidance Scheme

Abstract: With the pervasiveness of smartphones, mobile eHealthcare has attracted considerable attention in recent years. Disease risk prediction, as it can assist in predicting user's disease with big data analytics techniques, has become one of important topics in the field of e-Healthcare. However, if the privacy issue is not well addressed, disease risk predication cannot step into its flourish. Aiming at addressing this challenge, in this paper, we propose a new efficient and privacy-preserving pre-clinical guidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Evaluation done by [2] revealed that over 200 businesses created since 2010 are developing a diverse set of innovative tools to make better use of available healthcare information. As the technological capabilities and understanding advance, innovators are expected to develop even more interesting ideas for using big data, some of which could help substantially reduce the soaring cost of healthcare [3].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation done by [2] revealed that over 200 businesses created since 2010 are developing a diverse set of innovative tools to make better use of available healthcare information. As the technological capabilities and understanding advance, innovators are expected to develop even more interesting ideas for using big data, some of which could help substantially reduce the soaring cost of healthcare [3].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in [2], the protocol is much faster than publickey based protocols using homomorphic encryption. Since then, this protocol has been and is still used in many privacy-preserving solutions, e.g., [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], including support vector machines [17], facial expression classification [9], medical pre-diagnosis [18], and speaker verification [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…• We propose an e cient pre-clinical guidance service scheme (PGuide) [20] designed to provide on-the-go medical guidance service while preserving user privacy. With PGuide, users can personally conduct privacy-preserving pre-clinical diagnosis based on their health profiles [8], and obtain recommendation from trusted sources (e.g.…”
Section: Research Contributionsmentioning
confidence: 99%
“…On the other hand, the healthcare center owns the disease model (a 1 , a 2 , ..., a k ) and thresholds (t 1 , t 2 , ..., t l ). The disease risk score S for the user, can be computed by S = P k i=1 a i • x i [20,114,115]. We can calculate a user's disease risk by comparing the disease risk score and the thresholds (t 1 , t 2 , ..., t l ).…”
Section: Overviewmentioning
confidence: 99%